2014
DOI: 10.1109/tvlsi.2013.2278951
|View full text |Cite
|
Sign up to set email alerts
|

Control Principles and On-Chip Circuits for Active Cooling Using Integrated Superlattice-Based Thin-Film Thermoelectric Devices

Abstract: Superlattice thin-film thermoelectric coolers (TECs) are emerging as a promising technology for hot spot mitigation in microprocessors. This paper studies the prospect of ondemand cooling with advanced TECs integrated at the back of the heat spreader inside a package (integrated TEC). Using thermal compact models of the chip and package with integrated TECs, the control principles for TEC-assisted transient cooling are presented. The control principles are implemented in a 130-nm CMOS process and cosimulated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Long [7], [8]. However, the experimental demonstration of an on-chip TEC controller with programmable current source is not reported in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…Long [7], [8]. However, the experimental demonstration of an on-chip TEC controller with programmable current source is not reported in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…It showed that when the size of the TEC became smaller, increasing the thickness of the top metal contact and optimizing parameters such as the filling ratio and 3D size would enhance the cooling effect and the reliability of devices. Sullivan et al [17] designed a super-lattice TEC integrated with a controller and investigated its steady and transient cooling effect. The results showed that the power margin of the chip would increase by 12% compared to that at the steady state.…”
Section: Introductionmentioning
confidence: 99%
“…For example, with improvements in the chip manufacturing process, heat dissipation has emerged as a significant problem that restricts the development of high-performance chips and large power dissipation devices [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%